2006
DOI: 10.1177/154193120605000367
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Authority Allocation in Unmanned Aerial Vehicles

Abstract: The Ground Control Station (GCS) is a critical element in the control of Unmanned Aerial Vehicles (UAVs). The information provided by the GCS influences the operator's Situational Awareness (SA). In order to explore the consequences of authority on operator SA and overall performance, this research investigated the desired authority of two operator support functions that perform conflict detection and resolution in the time-critical domain. In the experiment, the Level of Authority (LoA) of these two functions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…In these domains, automation is crucial because the human operator is not embedded within the system (Tvaryanas, 2004), and hazardous events may interfere with human-robot interactions (e.g., communication breakdown and latencies). The design of authority sharing is therefore critical (Inagaki, 2003) because conflict between the robot and human operator could seriously compromise mission success (Parasuraman & Wickens, 2008;Van Ginkel, de Vries, Koeners, & Theunissen, 2006). Such problems have motivated researchers (Meyer, 2001;Parasuraman & Wickens, 2008;Rice, 2009) to study imperfect diagnostic automation (i.e., miss-prone vs. false alarm-prone automation).…”
Section: Introductionmentioning
confidence: 98%
“…In these domains, automation is crucial because the human operator is not embedded within the system (Tvaryanas, 2004), and hazardous events may interfere with human-robot interactions (e.g., communication breakdown and latencies). The design of authority sharing is therefore critical (Inagaki, 2003) because conflict between the robot and human operator could seriously compromise mission success (Parasuraman & Wickens, 2008;Van Ginkel, de Vries, Koeners, & Theunissen, 2006). Such problems have motivated researchers (Meyer, 2001;Parasuraman & Wickens, 2008;Rice, 2009) to study imperfect diagnostic automation (i.e., miss-prone vs. false alarm-prone automation).…”
Section: Introductionmentioning
confidence: 98%
“…This cooperation breakdown can lead to accidents with an airworthy airplane where the crew persists in solving a minor conflict (Billings, 1996) "instead of switching to another means or a more direct means to accomplish their flight path management goals" (Woods and Sarter, 2000, p. 347), and this can occur despite the onset of auditory alarms (Beringer and Harris, 1999). Such hazardous situations are not only relevant in aviation but also in the context of human supervisory control of unmanned vehicles (UVs) where careless design of authority sharing (Inagaki, 2003) degrades the human operator's performance leading to inadequate behaviors (Parasuraman and Wickens, 2008;Van Ginkel et al, 2006). Moreover, some authors (Meyer, 2001;Parasuraman and Wickens, 2008;Rice, 2009) revealed that unreliable diagnostic automation (i.e.…”
Section: Conflict In Humanesystem Interactions: a Complementary Metrimentioning
confidence: 99%